THE ROLE OF HALAL CERTIFICATION INSTITUTIONS IN ENSURING BUSINESS OPERATORS' COMPLIANCE WITH PRODUCT NAMING REQUIREMENTS IN INDONESIA’S HALAL CERTIFICATION PROCESS - Yadita, Devina; Sakti, Muthia (Universitas Islam Negeri Mataram, 2025)
A legal tool known as halal certification attests to a product's halal status and ensures compliance with Islamic law. Implementing halal certification involves more than inspection and testing; it also requires certifying bodies to ensure that business actors comply with product-naming rules during the certification process. The purpose of this study is to investigate human resource development in the halal certification process via the regular and self-declaration pathways established by BPJPH, MUI, and LPH, and to analyse the monitoring of the halal certification mechanism through these two channels. With a statute-based and case-based methodology, this study employs a normative juridical approach. Primary, secondary, and tertiary legal literature found through library research are the sources of the data used. The study's findings indicate that BPJPH, MUI, and LPH conduct more stringent oversight of the halal certification procedure through standard channels, involving Halal Auditors and Halal Supervisors who possess competency certifications in compliance with legal requirements. However, because the self-declaration pathway depends on the business owner's self-declaration and PPH Assistants' confirmation, it is typically more vulnerable to exploitation.